2016
DOI: 10.3899/jrheum.160866
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Classification and Renal Outcome in Patients with Antineutrophil Cytoplasmic Antibodies-associated Renal Vasculitis: A Study of 186 Patients and Metaanalysis

Abstract: We demonstrated the clinical utility of histopathologic classification in determining renal outcome in patients with AAV. Metaanalysis showed that patients with focal class had the best outcome while sclerotic class had the worst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 31 publications
4
66
0
Order By: Relevance
“…To date, reported predictors of renal outcome are mainly patients’ age, severe renal dysfunction and histopathological findings at presentation 1 2. Histopathological classification as defined by Berden et al was proposed to be helpful with the highest renal survival rates in the focal group and the poorest in the sclerotic group 3 4. Recently, Brix et al suggested the antineutrophil cytoplasmic antibody renal risk score (ARRS) to predict ESRD in patients with AAV 5.…”
mentioning
confidence: 99%
“…To date, reported predictors of renal outcome are mainly patients’ age, severe renal dysfunction and histopathological findings at presentation 1 2. Histopathological classification as defined by Berden et al was proposed to be helpful with the highest renal survival rates in the focal group and the poorest in the sclerotic group 3 4. Recently, Brix et al suggested the antineutrophil cytoplasmic antibody renal risk score (ARRS) to predict ESRD in patients with AAV 5.…”
mentioning
confidence: 99%
“…In a histologic sense, severity of acute lesions, such as glomerular crescents and fibrinoid necrosis, rather than chronic lesion-like glomerular sclerosis is well correlated with renal outcome and responsiveness of immunosuppressants in several renal vasculitides associated with AAV [29,33,34]. Classification of ANCA-associated glomerulonephritis based on renal biopsy results has been developed for the prognosis of renal vasculitis [29,33,34].…”
Section: Renal Involvement In Anca-associated Vasculitismentioning
confidence: 99%
“…As mentioned earlier, the renal outcome of ANCA-associated renal vasculitis is mainly related to GFR at onset time of renal disease and specific pathologic findings including several glomerular damages, interstitial fibrosis, and tubular atrophy rather than the serum ANCA level. However, according to several studies [33,34,37]. The treatment of ANCA-associated renal vasculitis is mainly composed of high-dose glucocorticoid and systemic cyclophosphamide for three months or six months in induction therapy.…”
Section: Renal Involvement In Anca-associated Vasculitismentioning
confidence: 99%
See 2 more Smart Citations